Effects of Visual Experience on the Human MT+ Functional Connectivity Networks: An fMRI Study of Motion Perception in Sighted and Congenitally Blind Individuals - Sani, Lorenzo; Ricciardi, Emiliano; Gentili, Claudio; Vanello, Nicola; Haxby, James V.; Pietrini, Pietro (Frontiers in Systems Neuroscience, 2010)
Human middle temporal complex (hMT+) responds also to the perception of non-visual motion in both sighted and early blind individuals, indicating a supramodal organization. Visual experience, however, leads to a segregation of hMT+ into a more anterior subregion, involved in the supramodal representation of motion, and a posterior subregion that processes visual motion only. In contrast, in congenitally blind subjects tactile motion activates the full extent of hMT+. Here, we used fMRI to investigate brain areas functionally connected with the two hMT+ subregions (seeds) during visual and tactile motion in sighted and blind individuals. A common functional connectivity network for motion processing, including bilateral ventral and dorsal extrastriate, inferior frontal, middle and inferior temporal areas, correlated with the two hMT+ seeds both in sighted and blind individuals during either visual or tactile motion, independently from the sensory modality through which the information was acquired. Moreover, ventral premotor, somatosensory and posterior parietal areas correlated only with the anterior but not with the posterior portion of hMT+ in sighted subjects, and with both hMT+ seeds in blind subjects. Furthermore, a correlation between middle temporal and occipital areas with primary somatosensory seeds was demonstrated across conditions in both sighted and blind individuals, suggesting a cortico-cortical pathway that conveys non-visual information from somatosensory cortex, through posterior parietal regions, to ventral extrastriate cortex. These findings expand our knowledge about the development of the functional organization within hMT+ by showing that distinct patterns of brain functional correlations originate from the anterior and posterior hMT+ subregions as a result of visual experience.